SECONDARY SCHOOL STUDENTS CONSTRUCTION OF KNOWLEDGE: THE CASE OF FRACTIONS DIVISION - Veronika Fitri Rianasari; Hongki Julie (Sanata Dharma University Yogyakarta, 2018)
Fractions are well known to be difficult to learn, but it is should not be surprising considering the complexity of the concepts involved. In working with fractions, children learn new rules that often conflict with well-established ideas about whole numbers. Many studies have revealed that fractions division has been thought to be the most complex of the mathematical operations in elementary mathematics. However, fractions and the operations have been recognized as an important foundation for the understanding of our number system. Therefore teachers should provide meaningful learning experiences that relate to division of fractions. This present study aimed to analyze secondary school students construction of knowledge in fractions division. This descriptive study was conducted with 44 seventh grade students in Pangudi Luhur Junior High School in Yogyakarta, Indonesia. During a one-week unit of lesson on division of fractions, students were given a task-based activity specifically designed to promote students understanding. Data sources in this study included observation of learning process and a pre and posttest of students conceptual knowledge and procedural computation skills. The result showed a significant improvement in students conceptual knowledge and procedural knowledge.DOI: https://doi.org/10.24071/ijiet.2018.020205